Epidemiological study of vibration syndrome in response to total hand-tool operating time. Issue 1 (February 1983) - Miyashita, K; Shiomi, S; Itoh, N; Kasamatsu, T; Iwata, H
Abstract : The correlation between the severity of vibration syndrome and hand-tool operating time in chain saw workers has been studied. The total chain saw operating time was calculated by using the equation: chain saw operating hours/day X days/year X years, and 266 chain saw operators were classified into four groups (0-2000 h, 2000-5000 h, 5000-8000 h, over 8000 h). Forty-six forestry workers not using chain saws were used as controls. The prevalence rates of symptoms were checked and statistically compared in each group. In the group with under 2000 hours' experience, symptoms were generally confined to tingling, numbness, or pain; with 2000-5000 hours peripheral nerve and circulatory disturbances, including Raynaud's phenomenon, and muscle and general body conditions were influenced to some degree; with 5000-8000 hours' functional changes were noted; while with over 8000 hours about half the operators suffered severely from functional or organic changes due to vibration.